2009
DOI: 10.1007/s11999-009-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

Infarct-associated Bone Sarcomas

Abstract: Sarcoma associated with bone infarct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 18 publications
0
45
0
1
Order By: Relevance
“…A bone infarction can occur owing to various conditions including corticosteroid therapy, hemoglobinopathy, alcoholism, Gaucher's disease, dysbaric disorders, trauma, infection, and metabolic disorders [1,2,6,9]. A bone infarction is not associated with a soft tissue mass and therefore it cannot be the only diagnosis in our case.…”
Section: Discussion and Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…A bone infarction can occur owing to various conditions including corticosteroid therapy, hemoglobinopathy, alcoholism, Gaucher's disease, dysbaric disorders, trauma, infection, and metabolic disorders [1,2,6,9]. A bone infarction is not associated with a soft tissue mass and therefore it cannot be the only diagnosis in our case.…”
Section: Discussion and Treatmentmentioning
confidence: 91%
“…Bone infarcts do not result in significant endosteal scalloping. When associated with MFH, curvilinear radiodensities of the underlying mature bone infarct can be seen blending into areas of permeative and lytic destruction attributable to the malignancy [2]. The osteonecrotic lesion frequently will appear larger than usually is seen, and usually is ill defined with cortical erosion, periosteal reaction, a pathologic fracture, and soft tissue extension [4,5,7,8,10,11,13].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…However bone infarcts are generally commonly associated with malignant fibrous histiocytomas and osteosarcomas [23]. Domson et al combining data from 57 non-GD patients reported that 69% of all tumors arising from bone infarcts were malignant fibrous histiocytomas, 17% were osteosarcomas, and 9% angiosarcomas [23]. Given that as many as 43% of GD patients have avascular necrosis and bone infarctions [24], it is surprising that no cases of malignant fibrous histiocytoma or osteosarcoma have been reported in literature to our knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…However bone infarcts are generally commonly associated with malignant fibrous histiocytomas and osteosarcomas [23]. Domson et al combining data from 57 non-GD patients reported that 69% of all tumors arising from bone infarcts were malignant fibrous histiocytomas, 17% were osteosarcomas, and 9% angiosarcomas [23].…”
Section: Discussionmentioning
confidence: 99%
“…Med., 2011, 225 (3), 215-220. © 2011 Tohoku University Medical Press An infarct-associated sarcoma is uncommon; approximately 70 cases in the world have been filed in the medical literature (Torres and Kyriakos 1992;Domson et al 2009). The pathogenesis of the malignant transformation remains obscure; however, the reparative tissue adjacent to infarct lesions is the assumed source of the sarcomatous transformation (Mirra et al 1974(Mirra et al , 1977.…”
mentioning
confidence: 99%